2019
DOI: 10.1523/eneuro.0421-18.2019
|View full text |Cite
|
Sign up to set email alerts
|

Sphingomyelin in Brain and Cognitive Development: Preliminary Data

Abstract: Sphingomyelin (SM) supports brain myelination, a process closely associated with cognitive maturation. The presence of SM in breast milk suggests a role in infant nutrition; however, little is known about SM contribution to healthy cognitive development. We investigated the link between early life dietary SM, later cognitive development and myelination using an exploratory observational study of neurotypical children. SM levels were quantified in infant nutrition products fed in the first three months of life … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
71
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(71 citation statements)
references
References 48 publications
0
71
0
Order By: Relevance
“…Previous research has implicated disturbances in sphingolipid balance in cognitive development (54,55), function (55), ageing (55,56) and AD (57) However, due to a lack of longitudinal metabolite data, we cannot rule out the possibility that later life sphingolipid levels may be a proxy for those of earlier life. In this regard, childhood cognition and education could be mediators of early life sphingolipid levels and later life cognitive function; or perhaps they may be linked by common genetic or environmental causes.…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…Previous research has implicated disturbances in sphingolipid balance in cognitive development (54,55), function (55), ageing (55,56) and AD (57) However, due to a lack of longitudinal metabolite data, we cannot rule out the possibility that later life sphingolipid levels may be a proxy for those of earlier life. In this regard, childhood cognition and education could be mediators of early life sphingolipid levels and later life cognitive function; or perhaps they may be linked by common genetic or environmental causes.…”
Section: Discussionmentioning
confidence: 90%
“…Previous research has implicated disturbances in sphingolipid balance in cognitive development (54,55), function (55), ageing (55,56) and AD (57). Sphingolipids are a lipid family comprised of sphingomyelins, ceramides and glycosphingolipids, and are present in large quantities in the CNS (57).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many previous reports have suggested that dietary PLs such as PC, PS, and SM are critical to maintain brain development and cognitive performance 12,41,42 . These lipids contain two fatty acids that are ester-linked to glycerol at sn-1 and sn-2, and a polar head group that is held at sn-3 by a phosphodiesterase bond 43 .…”
Section: Discussionmentioning
confidence: 99%
“…postsynaptic excitability or cortical gain ( Geisler and Albrecht, 1992 ; Abbott et al , 1997 ; Pi et al , 2013 ; Kanai et al., 2015 ; Mongillo et al , 2018 ). There is great interest in these neuroplastic changes because they are reminiscent of the critical period in brain development ( Schneider et al , 2019 ) and offer a potential target for interventions to promote and facilitate recovery after brain damage ( Starkstein and Robinson, 1997 ). Multiple factors may alter excitatory–inhibitory balance in perilesional tissue and enable repair ( Bansal et al , 2019 ) including changes in the uptake of neurotransmitters such as glutamate and serotonin and the release of growth factors that promote axonal sprouting in the first 2 or 3 weeks after damage.…”
Section: Introductionmentioning
confidence: 99%